PEMROGRAMAN SISTEM KEAMANAN WEB ADMINISTRATOR BERDASARKAN IP PUBLIK BERBASIS IOT (INTERNET OF THINGS) - Nurjanah, Nurjanah; Hamsir, Hamsir; Zein, Muhammad Ibnu; Oktafiani, Fitri (Sekolah Tinggi Teknologi MIGAS, 2024)
This research offers an innovative solution for implementing an IoT (Internet of Things) based web administrator security system. This research uses a wiring design that has been realized, the system can monitor and control access to the administrator dashboard based on the public IP address of the accessor. Using Lolin (WeMos) D1 R1 as a microcontroller and I2C LCD for data display, users can easily manage web access efficiently. Through the Arduino IDE application using the C/C++ programming language, this system can be set up with setup and loop functions, ensuring proper initialization and repeated processing of access requests. The test results of this system successfully demonstrated its ability to detect unauthorized access and block it with a fast response. An unknown IP will be detected on the system and turn on the alarm/buzzer and the public IP will appear on the LCD. Easy access control via tactical buttons works to block unauthorized access. This system also sends notifications via the Telegram application, providing greater convenience and control for users. In its development, this system can be applied and combined with various devices as a control and security system.